PENGEMBANGAN TEMA CINTA DALAM LIRIK-LIRIK LAGU JONAS BROTHERS - SUOTH, ENDA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2013)
Jonas Brothersâ€™ song lyrics which are about love become the data of this piece of writing. The development of Jonas Brothersâ€™ lyrics main theme, in this case love divided into the sub themes of friendship, unrevealed love, one sided love, waiting, regretting, and separating become the focus of this piece of writing. In terms of methodology, the â€œcontrast analysisâ€ is applicable for data collection. The theory based on Wellek and Warren, idea is a form of philosophy and it is leading into ideas. Perrineâ€™s definition of theme saying that theme belongs to a part of humanâ€™s experience. Whereas for the purpose of analyzing Robertsâ€™ paradigm including the descriptive method are applied. The result findings show that there are six sub themes which develop from the theme of love. The sub themes of friendship and unrevealed love dominate the whole writing.